1999
DOI: 10.1046/j.1365-2958.1999.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CesT, a chaperone for the type III secretion of Tir in enteropathogenicEscherichia coli

Abstract: SummaryThe locus of enterocyte effacement of enteropathogenic Escherichia coli encodes a type III secretion system, an outer membrane protein adhesin (intimin, the product of eae ) and Tir, a translocated protein that becomes a host cell receptor for intimin. Many type III secreted proteins require chaperones, which function to stabilize proteins, prevent inappropriate protein± protein interactions and aid in secretion. An open reading frame located between tir and eae, previously named orfU, was predicted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
193
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(206 citation statements)
references
References 46 publications
10
193
0
3
Order By: Relevance
“…A limited number of NF-T3SS chaperones are reported to be membrane-associated, such as CesD and CesT from EPEC (Elliott et al, 1999;Wainwright & Kaper, 1998), YscB from Yersinia (Jackson et al, 1998), SseA from Salmonella (Zurawski & Stein, 2003) and EscC from Ed. tarda (Zheng et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of NF-T3SS chaperones are reported to be membrane-associated, such as CesD and CesT from EPEC (Elliott et al, 1999;Wainwright & Kaper, 1998), YscB from Yersinia (Jackson et al, 1998), SseA from Salmonella (Zurawski & Stein, 2003) and EscC from Ed. tarda (Zheng et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the cognate chaperone is not absolutely required for protein secretion seems to be rather common for type III effectors in several pathogens (Parsot et al, 2003). Actually, there is evidence that Tir secretion is not strictly dependent on CesT as low levels of Tir can be detected in culture supernatants of cesT mutants (Elliot et al, 1999).…”
Section: Interaction Of Gapdh With the General Type III Chaperone Cestmentioning
confidence: 99%
“…In the case of EPEC, the LEE encoded type III secretion chaperone CesT was initially shown to bind and stabilize Tir within the bacterial cell (30,31); however, additional studies have demonstrated interactions with the effectors Map, EspF, and NleA (32)(33)(34). CesT is also required for the efficient in vitro type III secretion of other LEE and non-LEE type III effectors (33), suggesting that other chaperone-effector interactions may occur within the bacterium.…”
mentioning
confidence: 99%